The effectiveness of a smart system designed to detect prohibitions in supporting the duties of workers on the safety and security of sports stadiums in Iraq. - Tayeh Al-Majidi , Muhammad Bahir Ali; Salah Wahhab Shaker, (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to design and implement a smart electronic system to detect prohibitions in sports stadiums, and to identify the effectiveness of this smart system in its work, and to identify the relationship and impact of the effectiveness of the smart system in supporting the tasks of workers on the security and safety of sports stadiums, and the researchers adopted the descriptive approach to the method of linking relationships on A sample of three formations working on managing and organizing matches in sports stadiums from the honorific and stadium security section of the Iraqi National Olympic Committee, and stadium security section employees within the formations of the General Directorate for the Protection of Facilities and Characters in the Ministry of Interior, and Employing the stadium security and safety division within the formations of the youth and sports facilities section in the Ministry of Youth and Sports, randomly selected at a rate of (58.501%) to reach a number of its members (437) members of the total community of (747) individuals. The researchers designed an intelligent system to detect prohibitions from the following main parts: (Node MCU) chip, gas sensor, flame sensor, tilt sensor, metal detector, optical resistance, laser beam transmitter, small electrical metal wires, rechargeable battery, Breadboard, and Router MiFi) to be tight electronic control Using smartphones linked to a closed circuit on the international information network as it was done The adoption of two paper scales for the two research phenomena, to survey the opinions of workers after completing the design of the smart system and the use of this smart system project by the research sample in the various stadiums and sports halls and informing them of its work and operation on their own -V26) The conclusions and applications in that the designed smart system reveals the prohibitions threatening the security and safety of stadiums with high-precision technology through the efficiency of the specialized electronic sensors it contains, and fulfilled the aspirations of administrators and officials responsible for Ed The times of matches in stadiums and sports halls and the progress of organizing fans and controlling electronically using smartphones linked to the Internet (Internet). Its effect in reducing the risks of the main factors and causes that threaten the safety and security of sports stadiums